Alienation in Bian Zhilin's Fragment and Sherko Bekas's Now a Girl is My Homeland: A comparative literary analysis - Mariwan Hasan (Universitas Merdeka Malang, 2026)
Comparative studies of Chinese and Kurdish poetry remain scarce, particularly those exploring how poets from different historical and cultural contexts represent political disillusionment, identity fragmentation, and belonging. Addressing this gap, this study compares Bian Zhilin's Fragment and Sherko Bekas's Now a Girl is My Homeland through existentialist and postcolonial perspectives. Using a qualitative comparative literary approach based on close textual, thematic, and contextual analysis, the study examines how imagery, symbolism, silence, fragmentation, and representations of homeland construct meanings of alienation. The findings show that although the poems emerge from different political realities post-revolutionary China and the Kurdish experience of exile both portray alienation as an existential condition that reshapes identity and belonging. However, they differ in their poetic strategies: Zhilin employs silence, fragmentation, and introspection, whereas Bekas relies on symbolic representations of homeland, memory, and cultural resilience. By bringing Chinese and Kurdish poetry into dialogue, this study contributes to comparative literary scholarship by demonstrating how distinct poetic traditions converge in expressing universal experiences of loss, identity, and the search for meaning.